2021
DOI: 10.1007/s11469-021-00598-9
|View full text |Cite
|
Sign up to set email alerts
|

Anxious Attachment and Facebook Addiction: The Mediating Role of Need to Belong, Self-esteem, and Facebook Use to Meet Romantic Partners

Abstract: Background and aim: Although the beneficial aspects of web platforms such as Facebook are recognized, excessive social media use can lead to problematic or addictive behavior among a minority of users. Because anxious attachment has usually been analyzed in the relation to internet addiction, social media addiction, and Facebook intensity use, the main aim of the present study was to investigate the relationship between anxious attachment and Facebook addiction. A multiple-mediation model was proposed includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 66 publications
(70 reference statements)
1
12
0
Order By: Relevance
“…Related to the age variable, the results concurred with previous studies highlighting that SMA is prevalent among young people (Griffiths et al, 2014;Monacis et al, 2017). These 'digital natives' (and sometimes referred to as 'screenagers') (Griffiths, 2010) often use technology-based communication, including SM, in order to develop relationships, expand their social capital (Allen et al, 2014), and meet romantic partners (Stȃnculescu & Griffiths, 2021). In brief, the LPA findings showed that those LL -lower limit of the confidence interval, UL -upper limit.…”
Section: Tablesupporting
confidence: 84%
See 1 more Smart Citation
“…Related to the age variable, the results concurred with previous studies highlighting that SMA is prevalent among young people (Griffiths et al, 2014;Monacis et al, 2017). These 'digital natives' (and sometimes referred to as 'screenagers') (Griffiths, 2010) often use technology-based communication, including SM, in order to develop relationships, expand their social capital (Allen et al, 2014), and meet romantic partners (Stȃnculescu & Griffiths, 2021). In brief, the LPA findings showed that those LL -lower limit of the confidence interval, UL -upper limit.…”
Section: Tablesupporting
confidence: 84%
“…Other comorbidities have also been reported in the literature concerning SMA including depression (Best et al, 2014;Cheng et al, 2022;Hoare et al, 2016;McCrae et al, 2017), anxiety (Casale & Fioravanti, 2015;Lee-Won et al, 2015), and stress (Keles et al, 2020;Marino et al, 2017). In addition, studies examining problematic social media use have reported various predictors including depression and loneliness (Ho, 2022), social anxiety (Ali et al, 2022), poor subjective well-being (Marttila et al, 2021), dark triad traits (Monacis et al, 2020), attachment style (Monacis et al, 2017), narcissism (Andreassen et al, 2017), need to belong (Stȃnculescu & Griffiths, 2021), and 'selfitis' (i.e., obsessive selfie-taking; Lin et al, 2020). Analysis of the relationship between selfitis and social media addiction (Monacis et al, 2021) showed that there is a positive association between self-alienation and social media addiction, while the tendency to accept external influence and authenticity helped reduce the risk of addictive behavior.…”
Section: Social Media Addiction Psychosocial Correlates and Comorbid ...mentioning
confidence: 94%
“…Nevertheless, it's important to take into account the potentially harmful effects of problematic social media use through some online activities ( 17 , 31 ). Previous researches showed the problematic use of SNS was favored by unmet need to belong and anxious attachment style ( 32 , 33 ). Recent studies were conducted before the COVID-19 pandemic which had found daily stress had a significant effect on addictive social media ( 12 , 34 , 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…Even though previous studies have alluded to depressive traits as a contributing factor of PIU, the identified predictors of PIU in these studies have been low social connectedness (Quesnel et al, 2017 ; Romano et al, 2013 ; Kardefelt-Winther, 2014 ; Schimmenti & Caretti, 2010 ) and insecure attachment (Oldmeadow et al, 2013 ; Stănculescu & Griffiths, 2021 ). We found that depressive symptoms, avoidance attachment, and low social connectedness predicted problematic Internet use.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that individuals who fell in the anxious pre-occupied attachment category were more likely to excessively use social media platforms, like Facebook, in their attempt to maintain connections (Oldmeadow et al, 2013 ). A more recent study found a relationship between university students who report anxious attachment and Facebook addiction, which was mediated by an unmet need to belong, low self-esteem, and Facebook usage to meet romantic partners (Stănculescu & Griffiths, 2021 ). Further, those with fearful-avoidant attachment styles may prefer to interact over the Internet as it is perceived as “low-risk” when compared to face-to-face interactions (Baek et al, 2014 ).…”
mentioning
confidence: 99%